Nilai Ekonomi Pemanfaatan Rumput Program Kemitraan Konservasi di RPTN Kemalang SPTN Wilayah II Balai Taman Nasional Gunung Merapi - Ria Rizqi Nur Fadlilah; Agus Sunyata; Baroroh Wista Anggraeni (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
In the surrounding areas of Gunung Merapi National Park, grass harvesting is an inseperable part of the daily life of buffer zone communities. Natural growing grasses in the Kemalang resort area have been traditionally used for livestock feed, particularly through a conservation partnership scheme facilitated by the national park authority. In the context, natural resource management must adopt a sustainable development approach to maintain the balance between ecological, economic and sociocultural aspect especially by ensuring that utilization doesn’t exceed the land’s productive capacity. This research was conducted from august 25 to november 30 2022, within the conservation partnership area of kemalang resort, under the management of Gunung Merapi National Park region II. The study aimed to determine the productivity value, utilization levels and their economic value of grass within the conservation partnership scheme. A descriptive quantitative was used, involving field observations through the establishment of 42, 1x1m2 grass sampling plots. Quantitative data were also collected through structured intreviews to 42 landowner respondens selected via purposive sampling with a sampling intensity of 10%. Direct economic valuation was applied using actual market prices. The results show that grass productivity in the area reached 3.782.790,53 kg/year with an economic value of IDR111.867.536 /year. Meanwhile, thecommunity’s utilization reached 9.483.533,42 kg/year, with an economic valued at IDR7.808.895.167 /year. This significant gap reflects pressure on the regenerative capacity of grass resources, potentially threatening the area’s ecological functions. Sustainable non-timber forest product management is therefore essential to maintain a balance between conservation and the community needs.